Antibacterial aluminum profile and processing method thereof
By applying an antibacterial coating on the surface of the aluminum profile, the inorganic filler of cross-linked reinforced monomer and surface-modified mica powder is solved, and the microbial breeding problem of the aluminum profile of medical devices is achieved, achieving high adhesion, hardness and impact resistance Antibacterial properties, suitable for medical devices.
Patent Information
- Application Number
- CN202411361057.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The surface of the aluminum profile of medical devices is not effectively treated with antibacterial treatment and is prone to becoming a breeding ground for microorganisms, leading to the occurrence of hospital infections.
By coating an antibacterial coating on the surface of the aluminum profile, the cross-linked reinforced monomer and surface-modified mica powder are used as inorganic fillers to form an antibacterial coating with high adhesion, hardness and impact resistance, imparting antibacterial properties to the aluminum profile. .
Effectively prevent the coating from falling off and improving the stability of the coating, significantly improve the antibacterial properties of aluminum profiles, maintain a sterile environment, and is suitable for the medical device field.
Smart Images

Figure CN119242122A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to an antibacterial aluminum profile and a processing method thereof. Background Art
[0002] In the medical field, the choice of materials has a decisive influence on the performance, safety and service life of the equipment. Medical aluminum profiles occupy an important position in the manufacture of medical equipment due to their lightweight, biocompatibility, corrosion resistance and easy processing. However, with the complexity of the medical environment and the increase in patient safety requirements, medical devices, especially surgical instruments and rehabilitation equipment that are in direct contact with body fluids and drugs, can easily become a breeding ground for microorganisms if the surface is not effectively treated with antimicrobial agents. These microorganisms may be transmitted to patients through the equipment, leading to the occurrence of nosocomial infections. Therefore, it is particularly important to perform antimicrobial treatment on aluminum profiles for medical devices.
[0003] At present, it is common to impart antibacterial properties to aluminum profiles by coating the surface of the aluminum profiles with an antibacterial coating. For example, the invention patent with publication number CN115926563B discloses a preparation method and application of a high-strength composite antibacterial aluminum foil coating. The present invention modifies guanidine groups on acrylic ester monomers and utilizes the strong antibacterial properties of the guanidine groups to make the formed coating have good antibacterial properties. Therefore, the antibacterial properties of aluminum profiles can be improved by coating the surface with an antibacterial coating, which is beneficial to their further application in the field of medical devices. Summary of the invention
[0004] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide an antibacterial aluminum profile and a processing method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] An antibacterial aluminum profile comprises an aluminum profile substrate and an antibacterial coating; the antibacterial coating is formed by coating the antibacterial coating on the surface of the aluminum profile substrate and curing the coating; the antibacterial coating comprises the following components in parts by weight:
[0007]
[0008] The preparation method of the acrylic resin emulsion comprises the following steps:
[0009] Step 1: dissolve the emulsifier PCA-078 in purified water, add methyl acrylate, isooctyl acrylate, butyl acrylate and cross-linking reinforcing monomer to the uniform mixed solution, stir and mix evenly, and obtain a prepolymer emulsion;
[0010] Step 2, add ammonium persulfate and sodium bicarbonate to the prepolymer emulsion, after adding, stir mechanically to evenly, then gradually increase the temperature to 78-82°C, keep stirring for 6-9 hours, stop heating, stir and cool to room temperature, discharge, and obtain acrylic resin emulsion;
[0011] The preparation method of the antibacterial coating is as follows:
[0012] Add acrylic resin emulsion, inorganic filler, dispersant, film-forming aid and leveling agent into the mixer, control the speed to 1000-1500r / min, mechanically stir for 20-40min, then add defoamer into the mixer, continue stirring for 5-15min, then let stand to defoam, and the antibacterial coating can be obtained.
[0013] As a further embodiment of the present invention, the method for preparing the inorganic filler comprises the following steps:
[0014] Step S1, dispersing mica powder in toluene, and then adding polyglutamic acid and p-toluenesulfonic acid to the formed dispersion, after adding, controlling the temperature to 85-95° C., keeping the temperature for 4-8 hours under stirring, cooling and discharging, and centrifuging the solid material to obtain a mica powder modified intermediate;
[0015] Step S2, adding the mica powder modified intermediate into tetrahydrofuran, ultrasonicating to form a uniform dispersion, then adding 2,3-epoxypropyltrimethylammonium chloride and a phase transfer catalyst into the dispersion, adjusting the temperature to 60-65° C., stirring at the temperature for 2-6 hours, cooling and discharging the material, and obtaining an inorganic filler.
[0016] As a further embodiment of the present invention, in step S1, the number average molecular weight of the polyglutamic acid is 5000-10000.
[0017] As a further embodiment of the present invention, in step S2, the phase transfer catalyst is any one of tetrabutylammonium hydrogen sulfate, tetramethylammonium bromide or tetrabutylammonium bromide.
[0018] As a further embodiment of the present invention, in step 1, the mass ratio of the emulsifier PCA-078, methyl acrylate, isooctyl acrylate, butyl acrylate, cross-linking reinforcing monomer, ammonium persulfate and sodium bicarbonate is 0.5-1:15-25:3-5:5-10:1-3:0.1-0.5:0.5-1.
[0019] In the above technical scheme, p-toluenesulfonic acid is first used as a catalyst to catalyze the condensation of hydroxyl groups on the surface of mica powder with carboxyl groups in the polyglutamic acid structure, thereby modifying the polyglutamic acid on the surface of the mica powder. Then, a phase transfer catalyst is used to catalyze the condensation of active carboxyl substituents in the polyglutamic acid structure that do not participate in the esterification condensation and 2,3-epoxypropyltrimethylammonium chloride to undergo ring-opening esterification, thereby obtaining mica powder whose surface is modified with quaternary ammonium salt functional groups and macromolecular polyglutamic acid, i.e., an inorganic filler.
[0020] As a further solution of the present invention, in step 1, the preparation method of the cross-linking reinforcing monomer comprises the following steps:
[0021] Step SS1, the bridging agent and 1,4-dioxane are stirred and mixed to form a uniform solution, and then the activator is added to the solution, and after stirring at 40-50° C. for 1-2 hours, 4,4"-dibromoterphenyl is added, and the temperature is increased to 70-80° C., and the solution is kept warm for 8-12 hours under continuous stirring, and then the solvent is evaporated to obtain an intermediate product;
[0022] Step SS2, adding the intermediate product to toluene, mixing, and then adding the end-capping agent dimethylvinylchlorosilane. After adding, controlling the temperature to 60-70°C, maintaining for 2-4 hours, cooling and discharging the material, and the cross-linked reinforcing monomer can be obtained.
[0023] As a further embodiment of the present invention, in step 1, in step SS1, the bridging agent is bicyclo[2.2.2]octane-1,4-dimethanol; the molar ratio of the bridging agent to 4,4"-dibromoterphenyl is 1.1-1.2:1.
[0024] As a further solution of the present invention, in step one, in step SS1, the activator is a sodium hydroxide solution with a mass fraction of 15-30%.
[0025] In the above technical scheme, an activator is first used to activate the hydroxyl group in the bridging agent structure, and then 4,4"-dibromoterphenyl is used as a linker to continuously replace the bridging agent to form a macromolecular intermediate product connected by an ether bond. By controlling the dosage ratio of the two, the macromolecular intermediate product is made to be hydroxyl-terminated, and then the end-capping agent dimethylvinylchlorosilane is used to perform end-capping treatment on it, so as to obtain a polyether-type macromolecular substance with a terminal unsaturated olefinic substituent, that is, a cross-linking reinforcing monomer.
[0026] A method for processing an antibacterial aluminum profile comprises the following steps:
[0027] The first step is to use sandpaper to polish the aluminum profile base, then wash it with clean water and wait for it to dry completely;
[0028] The second step is to evenly coat the antibacterial coating on the surface of the aluminum profile substrate and cure it at a temperature of 80-100°C. After the curing is complete, take it out to obtain the antibacterial aluminum profile.
[0029] Beneficial effects of the present invention:
[0030] (1) The present invention prepares a cross-linked reinforcing monomer and copolymerizes and cross-links it with acrylic ester. On the one hand, the formed acrylic resin molecular chain can present a cross-linked network structure, which greatly improves the cohesive force and enhances the adhesion of the coating. In addition, the cross-linked reinforcing monomer structure contains a large number of ether bonds, so there are more functional groups in the structure that can generate hydrogen bonds with the adhered substrate, which can further improve the connection between the coating and the substrate and effectively prevent the coating from falling off. In addition, the cross-linked reinforcing monomer structure also contains a large number of rigid biphenyls and heterocyclic structures, which can make the coating more stable and more impact-resistant, prevent the coating from breaking due to slight bumps, and better protect the aluminum profile.
[0031] (2) The present invention uses mica powder with quaternary ammonium salt functional groups and macromolecular polyglutamic acid modified on the surface as an inorganic filler. First, the presence of macromolecular polyglutamic acid can interact with the acrylic resin molecular chain to form physical crosslinking, which can not only achieve uniform dispersion of the inorganic material mica powder in the coating, but also effectively exert its own reinforcement advantages in the form of a physical crosslinking core to improve the mechanical properties of the coating such as hardness. In addition, a large number of quaternary ammonium salt functional groups can give the coating a broad-spectrum antibacterial effect, allowing the aluminum profile to maintain a sterile environment.
[0032] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0034] Figure 1 This is the infrared analysis test diagram of the cross-linked reinforcing monomer. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Preparation Example 1
[0037] Preparation of acrylic resin emulsion:
[0038] Step 1: 0.3 g of bicyclo[2.2.2]octane-1,4-dimethanol and 1,4-dioxane are stirred and mixed to form a uniform solution, and then 10 mL of a 20% sodium hydroxide solution is added to the solution. After stirring at 45° C. for 2 h, 0.6 g of 4,4”-dibromoterphenyl is added, and the temperature is raised to 80° C. The mixture is kept warm for 9 h under continuous stirring, and then the solvent is evaporated to obtain an intermediate product.
[0039] Step 2: add 0.5g of the intermediate product to toluene, mix well, and then add 0.1g of the end-capping agent dimethylvinylchlorosilane. After the addition, control the temperature to 65°C, maintain for 3h, cool and discharge the material to obtain a cross-linked reinforcing monomer;
[0040] Figure 1 This is the infrared analysis test chart of the cross-linked reinforcing monomer, where 3067cm -1 The characteristic absorption peak at 3018cm is the characteristic absorption peak of carbon and hydrogen on the benzene ring. -1 The characteristic absorption peak at 2800-3000cm is the characteristic absorption peak of carbon and hydrogen of unsaturated olefinic substituents. -1 The characteristic absorption peaks appearing at 1000-1100cm -1 Characteristic absorption peaks of ether bonds and silicon-oxygen bonds overlapping each other appeared.
[0041] Step 3: Dissolve 0.6 g of emulsifier PCA-078 in 150 mL of purified water, add 20 g of methyl acrylate, 3.5 g of isooctyl acrylate, 8 g of butyl acrylate and 1.5 g of cross-linking reinforcing monomer to the resulting uniform mixture, stir and mix evenly to obtain a prepolymer emulsion;
[0042] Step 4: Add 0.3 g of ammonium persulfate and 0.6 g of sodium bicarbonate to the prepolymer emulsion. After adding, stir mechanically to make it uniform. Then gradually increase the temperature to 80°C. After stirring for 8 hours, stop heating, stir and cool to room temperature. Discharge the material to obtain an acrylic resin emulsion.
[0043] Preparation Example 2
[0044] Preparation of inorganic fillers
[0045] Step S1, dispersing 2.3g of mica powder in toluene, and then adding 8.5g of polyglutamic acid with a number average molecular weight of 10000 and 0.1g of p-toluenesulfonic acid to the formed dispersion. After the addition, the temperature is controlled to 95°C, kept warm for 6h under stirring, cooled and discharged, and the solid material is centrifuged to obtain a mica powder modified intermediate;
[0046] Step S2, adding 1.6 g of the mica powder modified intermediate into tetrahydrofuran, ultrasonicating to form a uniform dispersion, then adding 0.4 g of 2,3-epoxypropyltrimethylammonium chloride and 0.1 g of tetrabutylammonium bromide into the dispersion, adjusting the temperature to 60° C., stirring at the temperature for 3 h, cooling and discharging the material, and obtaining an inorganic filler.
[0047] The organic element content of the inorganic filler was tested using a PEG2000 element analyzer. The test results showed that the percentage of carbon element was 16.78%, and the percentage of nitrogen element was 4.16%.
[0048] Example 1
[0049] Preparation of antibacterial coating:
[0050] In terms of weight, 36 parts of acrylic resin emulsion, 1.5 parts of inorganic filler, 0.5 parts of dispersant sodium polyacrylate, 1 part of film-forming aid propylene glycol methyl ether and 0.5 parts of leveling agent sodium polyacrylate are added to a mixer, the speed is controlled at 1000r / min, and after mechanical stirring for 20 minutes, 0.5 parts of defoaming agent polydimethylsiloxane are added to the mixer. After the addition is completed, stirring is continued for 5 minutes, and then it is allowed to stand for defoaming to obtain an antibacterial coating.
[0051] The preparation method of the acrylic resin emulsion is shown in Preparation Example 1; the preparation method of the inorganic filler is shown in Preparation Example 2; the same applies below.
[0052] Example 2
[0053] Preparation of antibacterial coating:
[0054] In terms of weight, 38 parts of acrylic resin emulsion, 3 parts of inorganic filler, 1 part of dispersant sodium polyacrylate, 1.5 parts of film-forming aid propylene glycol methyl ether and 1 part of leveling agent sodium polyacrylate are added to a mixer, the speed is controlled at 1200r / min, and after mechanical stirring for 30 minutes, 0.8 parts of defoaming agent polydimethylsiloxane are added to the mixer. After the addition is completed, stirring is continued for 10 minutes, and then the mixture is allowed to stand for defoaming to obtain an antibacterial coating.
[0055] Example 3
[0056] Preparation of antibacterial coating:
[0057] By weight, 42 parts of acrylic resin emulsion, 3.2 parts of inorganic filler, 1.5 parts of dispersant sodium polyacrylate, 2 parts of film-forming aid propylene glycol methyl ether and 1.5 parts of leveling agent sodium polyacrylate are added to a mixer, the speed is controlled at 1500r / min, and after mechanical stirring for 40 minutes, 1 part of defoaming agent polydimethylsiloxane is added to the mixer. After the addition is completed, stirring is continued for 15 minutes, and then it is allowed to stand for defoaming to obtain an antibacterial coating.
[0058] Comparative Example 1
[0059] Preparation of antibacterial coating:
[0060] By weight, 38 parts of acrylic resin emulsion, 3 parts of mica powder, 1 part of dispersant sodium polyacrylate, 1.5 parts of film-forming aid propylene glycol methyl ether and 1 part of leveling agent sodium polyacrylate are added to a mixer, the speed is controlled at 120r / min, and after mechanical stirring for 30 minutes, 0.8 parts of defoaming agent polydimethylsiloxane are added to the mixer. After the addition is completed, stirring is continued for 10 minutes, and then the mixture is allowed to stand for defoaming to obtain an antibacterial coating.
[0061] Comparative Example 2
[0062] Preparation of antibacterial coating:
[0063] By weight, 38 parts of acrylic resin emulsion, 1 part of dispersant sodium polyacrylate, 1.5 parts of film-forming aid propylene glycol methyl ether and 1 part of leveling agent sodium polyacrylate are added to a mixer, the speed is controlled at 1200r / min, and after mechanical stirring for 30 minutes, 0.8 parts of defoaming agent polydimethylsiloxane are added to the mixer. After the addition is completed, stirring is continued for 10 minutes, and then it is allowed to stand for defoaming to obtain an antibacterial coating.
[0064] Comparative Example 3
[0065] Preparation of antibacterial coating:
[0066] By weight, 38 parts of acrylic resin emulsion, 3 parts of inorganic filler, 1 part of dispersant sodium polyacrylate, 1.5 parts of film-forming aid propylene glycol methyl ether and 1 part of leveling agent sodium polyacrylate are added to a mixer, the speed is controlled at 1200r / min, and after mechanical stirring for 30 minutes, 0.8 parts of defoaming agent polydimethylsiloxane are added to the mixer. After the addition is completed, stirring is continued for 10 minutes, and then it is allowed to stand for defoaming to obtain an antibacterial coating.
[0067] The preparation method of the acrylic resin emulsion is different from that of Preparation Example 1 in that no cross-linking reinforcing monomer is added, and the rest is the same.
[0068] Test Case
[0069] The antibacterial coatings in Examples 1 to 3 and Comparative Examples 1 to 3 were uniformly coated on the tinplate surface, and cured in a temperature environment of 100° C. The following performance tests were performed on the formed coating films:
[0070] Adhesion / Grade Hardness / H Impact resistance / kg·cm Antibacterial rate / % Example 1 0 5 45 99.5 Example 2 0 5 45 99.6 Example 3 0 5 45 99.4 Comparative Example 1 0 4 40 60.1 Comparative Example 2 0 2 30 59.8 Comparative Example 3 2 5 25 99.0
[0071] Note: Refer to standard GB / T 9286-2021 for adhesion test; refer to standard GB / T6739-2006 for pencil hardness test of paint film samples; refer to standard GB / T1732-2020 for impact resistance test of paint film samples; refer to standard GB / T 21866-2008 for antibacterial rate test, and the test bacteria are Escherichia coli.
[0072] From the analysis and test results, it can be seen that the coating formed by the antibacterial coating prepared in the embodiment of the present invention has strong adhesion, high hardness, good impact resistance, and exhibits excellent antibacterial properties, and can be applied to the field of medical aluminum profile equipment.
[0073] After replacing the inorganic filler with unmodified mica powder, it can be clearly seen that the hardness and impact resistance are slightly reduced, but the antibacterial performance is greatly reduced. This is because there are interface problems between the unmodified mica powder and the acrylic resin, which cannot fully exert its own advantages. In addition, the broad-spectrum antibacterial effect of the quaternary ammonium salt functional group is lost.
[0074] After the inorganic filler is directly removed, the hardness and impact resistance of the coating are further reduced because the advantages of mica powder cannot be utilized.
[0075] The antibacterial coating prepared using acrylic resin emulsion without adding cross-linking reinforcing monomer as raw material has poor adhesion and poor impact resistance.
[0076] The antibacterial coating in Example 2 of the present invention is used to prepare an antibacterial aluminum profile, which specifically includes the following steps:
[0077] The first step is to use sandpaper to polish the aluminum profile base, then wash it with clean water and wait for it to dry completely;
[0078] The second step is to evenly coat the antibacterial coating on the surface of the aluminum profile substrate and cure it at a temperature of 100°C. After the curing is complete, take it out to obtain the antibacterial aluminum profile.
[0079] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. An antibacterial aluminum profile, characterized in that: It includes an aluminum profile substrate and an antibacterial coating; the antibacterial coating is formed by coating the antibacterial coating on the surface of the aluminum profile substrate and curing it; the antibacterial coating includes the following components in parts by weight: The preparation method of the acrylic resin emulsion comprises the following steps: Step 1: dissolve the emulsifier PCA-078 in purified water, add methyl acrylate, isooctyl acrylate, butyl acrylate and cross-linking reinforcing monomer to the uniform mixed solution, stir and mix evenly, and obtain a prepolymer emulsion; Step 2, add ammonium persulfate and sodium bicarbonate to the prepolymer emulsion, after adding, stir mechanically to evenly, then gradually increase the temperature to 78-82°C, keep stirring for 6-9 hours, stop heating, stir and cool to room temperature, discharge, and obtain acrylic resin emulsion; The preparation method of the antibacterial coating is as follows: Add acrylic resin emulsion, inorganic filler, dispersant, film-forming aid and leveling agent into the mixer, control the speed to 1000-1500r / min, mechanically stir for 20-40min, then add defoamer into the mixer, continue stirring for 5-15min, then let stand to defoam, and the antibacterial coating can be obtained.
2. The antibacterial aluminum profile according to claim 1, characterized in that: The preparation method of the inorganic filler comprises the following steps: Step S1, dispersing mica powder in toluene, and then adding polyglutamic acid and p-toluenesulfonic acid to the formed dispersion, after adding, controlling the temperature to 85-95° C., keeping the temperature for 4-8 hours under stirring, cooling and discharging, and centrifuging the solid material to obtain a mica powder modified intermediate; Step S2, adding the mica powder modified intermediate into tetrahydrofuran, ultrasonicating to form a uniform dispersion, then adding 2,3-epoxypropyltrimethylammonium chloride and a phase transfer catalyst into the dispersion, adjusting the temperature to 60-65° C., stirring at the temperature for 2-6 hours, cooling and discharging the material, and obtaining an inorganic filler.
3. The antibacterial aluminum profile according to claim 2, characterized in that: In step S1, the number average molecular weight of the polyglutamic acid is 5000-10000.
4. The antibacterial aluminum profile according to claim 2, characterized in that: In step S2, the phase transfer catalyst is any one of tetrabutylammonium hydrogen sulfate, tetramethylammonium bromide or tetrabutylammonium bromide.
5. The antibacterial aluminum profile according to claim 1, characterized in that: In step 1, the mass ratio of the emulsifier PCA-078, methyl acrylate, isooctyl acrylate, butyl acrylate, cross-linking reinforcing monomer, ammonium persulfate and sodium bicarbonate is 0.5-1:15-25:3-5:5-10:1-3:0.1-0.5:0.5-1.
6. The antibacterial aluminum profile according to claim 1, characterized in that: In step 1, the preparation method of the cross-linked reinforcing monomer comprises the following steps: Step SS1, the bridging agent and 1,4-dioxane are stirred and mixed to form a uniform solution, and then the activator is added to the solution, and after stirring at 40-50° C. for 1-2 hours, 4,4"-dibromoterphenyl is added, and the temperature is increased to 70-80° C., and the solution is kept warm for 8-12 hours under continuous stirring, and then the solvent is evaporated to obtain an intermediate product; Step SS2, adding the intermediate product to toluene, mixing, and then adding the end-capping agent dimethylvinylchlorosilane. After adding, controlling the temperature to 60-70°C, maintaining for 2-4 hours, cooling and discharging the material, and the cross-linked reinforcing monomer can be obtained.
7. The antibacterial aluminum profile according to claim 6, characterized in that: In step 1, in step SS1, the bridging agent is bicyclo[2.2.2]octane-1,4-dimethanol; the molar ratio of the bridging agent to 4,4"-dibromoterphenyl is 1.1-1.2:
1.
8. The antibacterial aluminum profile according to claim 6, characterized in that: In step one, in step SS1, the activator is a sodium hydroxide solution with a mass fraction of 15-30%.
9. A method for processing an antibacterial aluminum profile as claimed in claim 1, characterized in that: The following steps are involved: The first step is to use sandpaper to polish the aluminum profile base, then wash it with clean water and wait for it to dry completely; The second step is to evenly coat the antibacterial coating on the surface of the aluminum profile substrate and cure it at a temperature of 80-100°C. After the curing is complete, take it out to obtain the antibacterial aluminum profile.
Citation Information
Patent Citations
Surface treatment liquid
CN111876782A
High-heat-resistance copolymerized silicon resin and preparation method thereof
CN113388120A
Antibacterial and mildew-proof aluminum profile powder coating and preparation method thereof
CN115386271A
Organic-inorganic antibacterial monomer composition and preparation method thereof, acrylic acid antibacterial emulsion and preparation method and application thereof
CN117089030A
Heat-resistant and aging-resistant rubber material and preparation method thereof
CN117820735A
Cited By
Antibacterial aluminum plate production control method and system based on large model
CN119644973A
Heat-insulating antibacterial coating for aluminum profile and preparation method of heat-insulating antibacterial coating
CN120349727A
